Novel Biomaterials for Tissue Engineering 2018 - Emmanuel Stratakis (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The concept of regenerating tissues, with properties and functions that mimic natural tissues, has attracted significant attention in recent years. It provides potential solutions for treating many diseases and other healthcare issues. To fully realize the potential of the approach, it is crucial to have a rational biomaterial design to create novel scaffolds, and other materials systems suitable for tissue engineering, repair and regeneration. Research advances on the topic include the design of new biomaterials and their composites, the scaffold fabrication via subtractive and additive manufacturing approaches, the development of implantable scaffolds for disease monitoring, diagnostics, and treatment, as well as the understanding of cells-biomaterial scaffolds interaction. This Special Issue, "Novel Biomaterials for Tissue Engineering", covers a selection of timely research activities in the field of biomaterials for tissue engineering and regeneration purposes. Promising findings on different approaches to design and develop new biomaterials, biomaterial systems and methods for tissue engineering, are presented and discussed. Recent advances in biofabrication techniques for tissue engineering are additionally demonstrated. The issue comprises a series of state-of-the-art experimental works, up-to-date review articles and commentaries.